Synergistic defects in pre-rRNA processing from mutations in the U3-specific protein Rrp9 and U3 snoRNA. Issue 7 (30th January 2020) - Clerget, Guillaume; Bourguignon-Igel, Valérie; Marmier-Gourrier, Nathalie; Rolland, Nicolas; Wacheul, Ludivine; Manival, Xavier; Charron, Christophe; Kufel, Joanna; Méreau, Agnès; Senty-Ségault, Véronique; Tollervey, David; Lafontaine, Denis L J; et al.
Abstract: U3 snoRNA and the associated Rrp9/U3-55K protein are essential for 18S rRNA production by the SSU-processome complex. U3 and Rrp9 are required for early pre-rRNA cleavages at sites A0, A1 and A2, but the mechanism remains unclear. Substitution of Arg 289 in Rrp9 to Ala (R289A) specifically reduced cleavage at sites A1 and A2. Surprisingly, R289 is located on the surface of the Rrp9 β-propeller structure opposite to U3 snoRNA. To understand this, we first characterized the protein-protein interaction network of Rrp9 within the SSU-processome. This identified a direct interaction between the Rrp9 β-propeller domain and Rrp36, the strength of which was reduced by the R289A substitution, implicating this interaction in the observed processing phenotype. The Rrp9 R289A mutation also showed strong synergistic negative interactions with mutations in U3 that destabilize the U3/pre-rRNA base-pair interactions or reduce the length of their linking segments. We propose that the Rrp9 β-propeller and U3/pre-rRNA binding cooperate in the structure or stability of the SSU-processome. Additionally, our analysis of U3 variants gave insights into the function of individual segments of the 5′-terminal 72-nt sequence of U3. We interpret these data in the light of recently reported SSU-processome structures.